2009
DOI: 10.1186/1471-2334-9-12
|View full text |Cite
|
Sign up to set email alerts
|

DNA restriction fragment length polymorphism analysis of Mycobacterium tuberculosis isolates from HIV-seropositive and HIV-seronegative patients in Kampala, Uganda

Abstract: BackgroundThe identification and differentiation of strains of Mycobacterium tuberculosis by DNA fingerprinting has provided a better understanding of the epidemiology and tracing the transmission of tuberculosis. We set out to determine if there was a relationship between the risk of belonging to a group of tuberculosis patients with identical mycobacterial DNA fingerprint patterns and the HIV sero-status of the individuals in a high TB incidence peri-urban setting of Kampala, Uganda.MethodsOne hundred eighty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
4
6
1
Order By: Relevance
“…The clinical care and close follow-up provided in a clinical cohort (10) might have further reduced transmission and might explain the lower clustering in HIV-infected patients, compared to HIV-negative patients. Of note, TB among the HIV-infected population was at least partly due to transmissions from HIVnegative individuals, consistent with reports from countries with high TB and HIV burdens (2).…”
Section: Discussionsupporting
confidence: 74%
“…The clinical care and close follow-up provided in a clinical cohort (10) might have further reduced transmission and might explain the lower clustering in HIV-infected patients, compared to HIV-negative patients. Of note, TB among the HIV-infected population was at least partly due to transmissions from HIVnegative individuals, consistent with reports from countries with high TB and HIV burdens (2).…”
Section: Discussionsupporting
confidence: 74%
“…The number of IS6110 copies ranged from 1 to 20 and the frequency of occurrence of IS6110 bands was similar between the two serogroups. The most prevalent pattern observed had 14 copies of IS6110 with the same distribution comparing HIV seropositive and HIV seronegative patients (Asiimwe et al, 2009). …”
Section: Tuberculosis Low Copy Number Strains (Lcs) and High Copy Numentioning
confidence: 99%
“…Several studies illustrate the situation in the highest TB incidence areas, such as two areas of India (Shanmugam et al, 2011;Purwar et al, 2011) or Uganda (Asiimwe et al, 2009). Other study that gives an overview of the distribution of genotypes of M. tuberculosis in Korea, found that drug resistance phenotypes were more strongly associated with Beijing family (see part 4.1.3).…”
Section: Recent Transmission and Population Studiesmentioning
confidence: 99%
“…Two approaches have been used to define MTB transmission in a community. The first uses MTBC phylogenetic clustering to signify on-going transmission (recent transmission) and the presence of unique strains as indicators of reactivation of latent TB infections [ 4 , 14 , 15 ]. A second approach defines transmission through pediatric TB, since children progress faster from recent MTB infection to disease than adults, in part because of immune system immaturity resulting in rapid disease progression rather than latency [ 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%